Pengaruh Tingkat Pendidikan dan Pelatihan terhadap Prestasi Kerja Karyawan Hotel Mauve Palembang - Sali, Yopi Okta; Halin, Hamid; Handayani, Susi (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
The intention of this study is to analyze the effect of the level of education and training on the work performance of hotel employees Mauve Palembang. The sample was collected by the saturated sample technique. Data of 43 respondents was collected through documentation and questionnaires. This study implements multiple linear regression method to analyze the data. The results of the investigation prove that in part, both the level of education and training have a significant positive effect on employee performance. This fact is useful for Hotel Mauve Palembang. To improve employee performance, the company must consider the level of education and training factors together.